Prevalence and factors affecting work-related musculoskeletal disorders among faculty members at Northeastern Universities in Thailand - Kaewjunda, Jureebhorn; Jiraponkul , Chananya; Swangnetr Neubert , Manida; Limmongkon , Yuparat (International Journal of Occupational Safety and Health, 2025)
Introduction: Work-related musculoskeletal disorders (WMSDs) are a leading cause of disability globally. In Thailand, WMSD incidence is high among people in several occupations. University faculty members who regularly use computers for long hours are an at-risk group. The aim of study is to determine prevalence and risk factors of WMSD for targeted interventions. Methods: This cross-sectional analytical study collected data online via Google Forms from 640 university faculty members between November 2023 and March 2024 and analyzed them using a General Linear Mixed Model (GLMM). Results: This study revealed a 58.9% prevalence of severe and very severe WMSDs in the neck, shoulders, and upper back. Significant risk factors of WMDs (p<0.001) included gender, stress, poor posture, and use of non-ergonomic workstations. Women were at 1.94 times greater risk of WMSDs than men. Those with severe stress were 4.80 times more likely to experience WMSDs than people with moderate stress. Faculty with inappropriate postures had a 2.67 times higher risk of WMSDs, and non-ergonomic workstations increased WMSD likelihood by 1.65 times. Conclusion: The prevalence of severe and very severe WMSDs was almost high, and four factors that contribute to WMSDs among university faculty members are gender, severe stress, poor posture, and use of non-ergonomic workstations. Faculty should be made aware of the high prevalence of WMSDs, take preventative measures in stress management, and use appropriate postures. Universities should provide ergonomic workstations and educate faculty on the risk factors associated with WMSD.